Geometric properties of Wright function - Sudhananda Maharana; Jugal K. Prajapat; Deepak Bansal (Mathematica Bohemica, 2018)
In the present paper, we investigate certain geometric properties and inequalities for the Wright function and mention a few important consequences of our main results. A nonlinear differential equation involving the Wright function is also investigated.